Molecular magnetic resonance imaging of acute vascular cell adhesion molecule-1 expression in a mouse model of cerebral ischemia - Hoyte, Lisa C.; Brooks, Keith J.; Nagel, Simon; Akhtar, Asim; Chen, Ruoli; Mardiguian, Sylvie; McAteer, Martina A.; Anthony, Daniel C.; Choudhury, Robin P.; Buchan, Alastair M.; Sibson, Nicola R. (Journal of cerebral blood flow & metabolism, 2010)
The pathogenesis of stroke is multifactorial, and inflammation is thought to have a critical function in lesion progression at early time points. Detection of inflammatory processes associated with cerebral ischemia would be greatly beneficial in both designing individual therapeutic strategies and monitoring outcome. We have recently developed a new approach to imaging components of the inflammatory response, namely endovascular adhesion molecule expression on the brain endothelium. In this study, we show specific imaging of vascular cell adhesion molecule (VCAM)-1 expression in a mouse model of middle cerebral artery occlusion (MCAO), and a reduction in this inflammatory response, associated with improved behavioral outcome, as a result of preconditioning. The spatial extent of VCAM-1 expression is considerably greater than the detectable lesion using diffusion-weighted imaging (25% versus 3% total brain volume), which is generally taken to reflect the core of the lesion at early time points. Thus, VCAM-1 imaging seems to reveal both core and penumbral regions, and our data implicate VCAM-1 upregulation and associated inflammatory processes in the progression of penumbral tissue to infarction. Our findings indicate that such molecular magnetic resonance imaging (MRI) approaches could be important clinical tools for patient evaluation, acute monitoring of therapy, and design of specific treatment strategies.
Gesehen am 25.04.2023